Impression of nonlinear radiation and Stefan blowing on the magneto cross nano-Williamson fluid above exponentially stretching sheet - Musharafa Saleem; Majid Hussain (Results in Engineering, 2023)
In order to investigate the impacts of mixed convection, electromagnetic force, and nonlinear thermal radiation on the nano-Williamson fluid (NWF) (Williamson fluid as a base fluid with nanoparticles) on an exponential stretched surface placed in a porous medium, this work considers the effects of both heat absorption-generation and Joule heating. However, consideration is also given to Stefan blowing in combination with Brownian motion and thermophoresis factors. By using similarity transformations and non-dimensional variables, the set of non-linear partial differential equations (PDEs) leading the study of fluid flow is converted into a system of ordinary differential equations (ODEs), which then numerically solved by the bvp4c built in MATLAB package. Additionally, the effects of the acquired relevant factors on the distributions of velocity, nanoparticles-concentration, and temperature have been investigated through graphical arrangements in order to give each parameter a physical meaning. The comparative values of skin friction and Nusselt number for dissimilar values of λ and S (Stefan blowing cases) are tabulated in Tables 1–4 respectively.